PANEL DATA REGRESSION ANALYSIS FOR MODELING THE HUMAN DEVELOPMENT INDEX IN NORTH SULAWESI PROVINCE - Abdussamad, Siti Nurmardia; Adityaningrum, Amanda; Payu, Muhammad Rezky Friesta (Parameter: Journal of Statistics, 2024)
The regression analysis is a technique used in hypothesis testing to determine the impact of one variable on another. This study uses Panel Data Regression Analysis, which combines cross-sectional and time series data. This study aims to analyze the impact of Life Expectancy, Income Per Capita, Expected School Years, and Average School Years on the Human Development Index. According to the result of the analysis, the Common Effect Model (CEM), which used Ordinary Least Squares (OLS) estimation, was the most suitable model. The equation obtained is . Moreover, according to the significance test, all independent variables were significantly related to the dependent variable